PELATIHAN PRAKTIKUM KIMIA SKALA KECIL ELEKTROLISIS AIR UNTUK GURU KIMIA DI WAE NAKENG, LEMBOR, NUSA TENGGARA TIMUR - Pamenang, Fransisca Ditawati Nur; Harta, Johnsen; Ratri, Monica Cahyaning; Wijayanti, Lucia Wiwid; Octaviani, Laurensia; Anggreni, Viktoria Cosinta; Surianti, Yosefina Ermi (ABDIMAS ALTRUIS: Jurnal Pengabdian Kepada Masyarakat, 2023)
Practicum is an activity that cannot be separated from chemical learning. Chemistry learning can be more meaningful through attractive practicum activities. One obstacle that arises in the implementation of the practicum is the availability of adequate practicum materials and tools. Small-scale chemistry practicum can overcome this obstacle, which is in the form of the use of materials that are environmentally friendly and available in the surrounding environment, as well as simple practicum tools that can be used. One of the small-scale chemistry practicums trained is the water electrolysis practicum. Simple practicum using sodium sulfate and water, able to explain the electrolysis of water well. Through this small-scale chemistry practicum training, teachers are expected to have the skills to carry out simple practicums and develop other practicum topics while still paying attention to the scientific field. Through this small-scale-based chemical practicum training, there is an increase in the mastery of the concept shown by an increase in the average score from 30.67 to 73.33. The teachers give a positive response regarding the implementation of this training activity.